Evolution of Murine α(1)-Proteinase Inhibitors: Gene Amplification and Reactive Center Divergence - Rheaume, Carol (J Mol Evol, 1994)
The organization and sequence of genes encoding the α(1)-proteinase inhibitor (α(1)PI), a major serine proteinase inhibitor of the mammalian bloodstream, have been compared in several species, including murine rodents (genus Mus). Analysis of gene copy number indicates that amplification of α(1)PI genes occurred at some time during evolution of the Mus genus, leading to fixation of a family of about three to five genes in several existing species (e.g., M. domesticus and M. saxicola), and only a single gene in others (e.g., M. caroli). A phylogeny for the various mammalian α(1)PI mRNAs was constructed based upon synonymous substitutions within coding regions. The mRNAs in different murine species diverged from a common ancestor before the formation of the first species lineages of the Mus genus, i.e., about 10–13 million years ago. Thus, α(1)PI gene amplification must have occurred prior to Mus speciation; gene families were retained in some, but not all, murine species. The reactive center region of the α(1)PI polypeptide, which determines target protease specificity, has diverged rapidly during evolution of the Mus species, but not during evolution of other mammalian species included in the analysis. It is likely that this accelerated evolution of the reactive center, which has been noted previously for serine proteinase inhibitors, was driven by some sort of a positive Darwinian selection that was exerted in a taxon-specific manner. We suggest that evolution of α(1)PI genes of murine rodents has been characterized by both modification of gene copy number and rapid reactive center divergence. These processes may have resulted in a broadened repertoire of proteinase inhibitors that was evolutionarily advantageous during Mus speciation.